Psychiatrists' work with sickness certification: frequency, experiences and severity of the certification tasks in a national survey in Sweden - Nilsson Gunnar H; Arrelöv Britt; Lindholm Christina; Ljungquist Therese; Kjeldgård Linnea; Alexanderson Kristina (BMC, 2012)
Abstract Background Many psychiatrists are involved in sickness certification of their patients; however, there is very limited knowledge about this aspect of their work. The objective of this study was to explore frequencies of problematic issues in the sickness certification tasks and experiences of severity regarding these problematic issues among psychiatrists. Methods A cross-sectional nationwide questionnaire study to all physicians in Sweden. The 579 specialists in psychiatry who answered the questionnaire, were under 65 years of age, worked mainly in psychiatric care, and had consultations involving sickness certification at least once a week were included. Results The frequency of problematic sickness certification consultations a few times per year or more often was considered by 87.3% of the psychiatrists; 11.7% handle such cases at least once a week. A majority (60.9%) reported 'not having enough time with the patient' at least once a week. The psychiatrists had access to several categories of professionals in their daily work. More than one third certified unnecessarily long sick-leave periods at least once a month due to waiting times for Social Insurance Office investigations or for treatments or investigations within health care. Conclusion The majority found it problematic to assess the level and duration of work incapacity, but also other types of problems like unnecessarily long sick-leave periods due to different types of waiting times. The findings have implications for different kinds of organisational and managerial support and training in sickness certification issues, like guidance to assess the level and duration of work incapacity.